Age and sex-related differences of pulp chamber size in mandibular second molars - Emre Bodrumlu; Ersan Cicek; Cihad Dundar (Wolters Kluwer Medknow Publications, 2013)
Aim: The aim of this study was to compare the size of the pulp chamber in mandibular second molars with the gender and age by means of panoromic radiographs. Materials and Methods: In this study, 200 panoromic radiographs of patients were randomly selected from the archives of the Faculty of Dentistry of Ondokuz Mayis University. The radiographs of the patients were measured under a stereomicroscope and categorized according to the gender and age. Results: Statistically differences were found in the mean sizes of pulp chamber between the groups under and above the age of 30 years (P < 0.05). There were significant differences in terms of "the distance between the tip of the lingual cusp to the roof of the pulp chamber", "the distance between the tip of the lingual cusp to the floor of the pulp chamber" and "the distance from the tip of the lingual cusp to the closest point of the furcation" between the male and female genders (P < 0.05). Conclusion: It is concluded that the pulp chamber can be exposed easily in female patients, because it is less shallow than males. However, the size of pulp chamber reduces after the age of 30 years in both the genders.